Do Asian EFL teachers use humor in the classroom? A case study of Vietnamese EFL university teachers. (October 2016) - Petraki, Eleni; Pham Nguyen, Huy Hoang
Abstract: This study examined university teachers' perceptions of the role of humor in English as a Foreign Language (EFL) teaching, teachers' practices of humor use, and teachers' preferences regarding humor types in the context of Vietnam. An ethnographic approach was employed in this study, combining observations, fieldnotes and interviews. The findings revealed that teachers acknowledged several beneficial functions of humor in EFL teaching. All teachers used humor in their teaching, or claimed that they did so. The three most preferred types of humor are humorous comments, jokes, and funny stories, employed to lighten the atmosphere and increase the teachers' immediacy. Teachers' perceptions about their practices and preferred types of humor provide insights into their readiness to adopt humor in the classroom. This research raises awareness of how humor can be integrated in language teaching and provides recommendations for effective classroom use.